A population-based study on the prevalence and factors associated with obesity in Selangor - Gyanchand Rampal, Lekhraj Rampal; Lekhraj Rampal, Sanjay Rampal; Md. Zain, Azhar; Mohd Sidik, Sherina; Ambigga, D.; A., Rahimah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2006)
Objective: This study was conducted to determine prevalence and factors associated with obesity in Selangor, Malaysia. Methods: A population-based cross-sectional study was conducted in all districts of Selangor State. All individuals, 15 years and above in the selected households, were included. A pre-tested structured questionnaire was used to collect the data. Weight was recorded using TANITA model HD-309 and height was measured using SECA Body meter Model 208. Statistical analysis was performed using Stata 8.2 taking into account the complex survey design. Results: The overall mean age of the 2219 respondents was 36.6(95% CI 35.7 – 37.6) years. There was no significant difference in the mean age of the males and females (p=0.697). The majority of the respondents were Malays (52.9%), followed by Chinese (30.9%), Indians (15.4%) and other races (0.9%). The overall mean BMI was 24.1 kg/m2 (95% CI=23.8- 24.4). The overall prevalence of obesity was 12.2% (95% CI 10.6%, 14.0%). There was no significant difference in the prevalence of obesity in the males compared to females (p>0.05). The prevalence of obesity increased with age up to the ages of 40-59 years and then decreased after 60 years. The highest prevalence of obesity was in the 40-59 years age groups in both sexes. The overall prevalence of obesity was significantly higher amongst the Malays (15.2%) compared to the Indians (11.6%) and Chinese (7.3%). Multivariate logistic regression analysis showed that only age and ethnicity were associated with obesity. Sex and educational level were not associated with obesity.